Mining Technology - Hammond, Andrew; Donnelly, Brendan; Ashwath, Nanjappa (IntechOpen, 2022)
Mining is essential for extracting natural resources. However, it is costly, potentially dangerous if poorly managed, and is perceived by some to be an environmentally unfriendly process. This book provides a comprehensive overview of mining technology with case examples and research. Chapters discuss a diversity of topics, including sonic drilling, quality assessment of rock bolts, block cave mine ventilation, microwave radar surveillance, safety management of tailings, and monitoring radon gas in underground mines.